Endometrial Stromal Hyperplasia: An Underrecognized Condition - Efthimios Sivridis; Gerasimos Koutsougeras; Alexandra Giatromanolaki (Case Reports in Pathology)
Hyperplasia of the endometrial stroma is a poorly recognized lesion, lacking widespread recognition with most, if not all, such cases sequestrated in the literature as endometrial stromal nodules or low-grade endometrial stromal sarcomas. In this paper, we describe three examples of “endometrial stromal hyperplasia” which have a remarkable morphological similarity with the normally proliferating endometrial stroma and the endometrial stromal neoplasms, but which also possess subtle, but sufficient, differences to justify their taxonomic separation.